Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.neurobiolaging.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation endproducts (RAGE) deficiency protects against MPTP toxicity

Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder of unknown pathogenesis characterized by the loss of nigrostriatal dopaminergic neurons. Oxidative stress, microglial activation and inflammatory responses seem to contribute to the pathogenesis. The receptor for advanced glycation endproducts (RAGE) is a multiligand receptor of the immunoglobulin superfamily of cell surface molecules. The formation of advanced glycation end products (AGEs), the first ligand of RAGE identified, requires a complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 51 publications
9
63
0
Order By: Relevance
“…However, aberrant apoptosis has been involved in several neurodegenerative conditions including Parkinson's disease, Huntington disease, and AD (Ghavami et al, 2014;Meng et al, 2013;Teismann et al, 2012). Our study also confirm that apoptosis occurs in SH-SY5Y cells and primary neurons exposed to Ab.…”
Section: Discussionsupporting
confidence: 81%
“…However, aberrant apoptosis has been involved in several neurodegenerative conditions including Parkinson's disease, Huntington disease, and AD (Ghavami et al, 2014;Meng et al, 2013;Teismann et al, 2012). Our study also confirm that apoptosis occurs in SH-SY5Y cells and primary neurons exposed to Ab.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, recent in vitro studies have even shown that AGEs induce the aggregation of α-syn in vitro (Lee et al, 2009;Padmaraju et al, 2011). The pathogenesis of the disease remains largely unclear; however, a few potential molecular contributors such as RAGE have been proposed (Teismann et al, 2012;Gao et al, 2014). RAGE has been found in neuronal Lewy bodies, whose presence is indicative of oxidative stress and neuroinflammation (Dalfo et al, 2005).…”
Section: Rage In Parkinson's Diseasementioning
confidence: 99%
“…First, the same AGER rs2070600 SNP that was implicated in CA1 atrophy during AD, was also correlated to the highest risk for PD development of all known AGER SNPs in a Turkish cohort GWAS (N=174 PD patients and N=150 healthy controls) [89]. In addition, when compared to healthy controls, PD patients have recently been shown to possess higher concentrations of RAGE ligands S100B and HMGB1 in the substantia nigra and cerebral spinal fluid (CSF) [90][91][92]. In rodent models, numerous studies have indicated that animals derive prominent protection from PD-like impairments when RAGE signaling was blocked through genetic ablation of S100b/Ager or by the administration of a RAGE inhibitor, FPS-ZM1, a BBB permeable, high affinity, multimodal blocker of RAGE [90].…”
Section: Rage and Parkinson's Disease Another Manifestation Of Cellumentioning
confidence: 98%